DETERMINAN DARI PENCEGAHAN KECURANGAN PADA LPD - I Gusti Ayu Tiara Dwi Cahyani; I Wayan Kartana; I Putu Gde Chandra Artha Aryasa (Jurnal Riset Akuntansi Warmadewa, 2024)
Factors influencing fraud prevention include corporate governance, the effectiveness of internal controls, and individual morality. This study aims to empirically examine the impact of governance, internal control effectiveness, and individual morality on the determinants of fraud prevention within Village Credit Institutions (LPD) across the Selat District, Karangasem Regency. This research employs a quantitative approach with a causal research design. The sample consists of employees from LPDs in the Selat District who meet specific sample criteria, selected through purposive sampling, resulting in a sample size of 75 respondents. Data analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings of this study indicate that governance, the effectiveness of internal control, and individual morality significantly influence the determinants of fraud prevention.